2008
DOI: 10.1210/er.2008-0009
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Metabolic Consequences of Fatty Liver

Abstract: Type 2 diabetes and cardiovascular disease represent a serious threat to the health of the population worldwide. Although overall adiposity and particularly visceral adiposity are established risk factors for these diseases, in the recent years fatty liver emerged as an additional and independent factor. However, the pathophysiology of fat accumulation in the liver and the cross-talk of fatty liver with other tissues involved in metabolism in humans are not fully understood. Here we discuss the mechanisms invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
360
3
27

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 470 publications
(401 citation statements)
references
References 340 publications
11
360
3
27
Order By: Relevance
“…This extent of change is outside the coefficient of variation for this technique. 1 The largest study to quantify changes in hepatic triglyceride concentration with lifestyle intervention was undertaken by Kantartzis et al 2 In overweight and obese men and women who achieved a 3.5% reduction in body weight with diet and exercise therapy, hepatic triglycerides decreased by 35% after 9 months in those with liver fat >5.56% at baseline. This benefit was associated with significant improvement in cardiorespiratory fitness.…”
Section: Effect Of Weight Loss Via Lifestyle Modification In Nafldmentioning
confidence: 99%
See 2 more Smart Citations
“…This extent of change is outside the coefficient of variation for this technique. 1 The largest study to quantify changes in hepatic triglyceride concentration with lifestyle intervention was undertaken by Kantartzis et al 2 In overweight and obese men and women who achieved a 3.5% reduction in body weight with diet and exercise therapy, hepatic triglycerides decreased by 35% after 9 months in those with liver fat >5.56% at baseline. This benefit was associated with significant improvement in cardiorespiratory fitness.…”
Section: Effect Of Weight Loss Via Lifestyle Modification In Nafldmentioning
confidence: 99%
“…(HEPATOLOGY 2010;52:370-381) N onalcoholic fatty liver disease (NAFLD) affects 30% of adults and a majority of obese individuals. 1 In addition to increasing morbidity and mortality from liver disease and cancer, excess liver fat is an independent risk factor for cardiovascular disease, insulin resistance, prediabetes and type 2 diabetes. 1 Thus, strategies to modulate the burden of NAFLD are likely to have benefits beyond attenuating liver disease to the broader realm of obesity-related cardiometabolic risk reduction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased lipogenesis has been implicated in the pathogenesis of hepatic steatosis and insulin resistance (27 ). The DNL index (16:0/18:2), which represents the main product of DNL and an essential fatty acid that originates from dietary lipids, has been proposed as a tool to assess fatty acid synthesis in humans (13,23 ).…”
Section: Expression Of Lipogenic Genesmentioning
confidence: 99%
“…Hence, the increased intra-hepatic cytokine production that occurs in NAFLD/NASH is likely to play a pathogenic role also in the development of extra-hepatic complications, such as CVD and CKD. shown that potential mediators of vascular and renal damage occur more frequently in patients with NAFLD, regardless of whether or not they also have T2DM [45][46][47][48] . Increased oxidative stress, reactive oxygen species and the inflammatory response are thought to be all important pathogenic factors that are not only involved in the development of NASH, but are also pathogenic factors for the development and progression of CKD.…”
Section: Predisposing Factors Contributing To Nash: Diet Insulin Resmentioning
confidence: 99%